The subcompartmented oxphosomic model of the phosphorylating system organization in mitochondria - I. V. Ukolova (Вавиловский журнал генетики и селекции)
The oxidative phosphorylation (OXPHOS) system of mitochondria supports all the vitally important energyconsuming processes in eukaryotic cells, providing them with energy in the form of ATP. OXPHOS enzymes (complexes I–V) are located in the inner mitochondrial membrane, mainly in the cristae subcompartment. At present, there is a large body of data evidencing that the respiratory complexes I, III2 and IV under in vivo conditions can physically interact with each other in diverse stoichiometry, thereby forming supercomplexes. Despite active accumulation of knowledge about the structure of the main supercomplexes of the OXPHOS system, its physical and functional organization in vivo remains unclear. Contemporary models of the OXPHOS system’s organization in the inner membrane of mitochondria are contradictory and presume the existence of either highly organized respiratory strings, or, by contrast, a set of randomly dispersed respiratory supercomplexes and complexes. Furthermore, it is assumed that ATP-synthase (complex V) does not form associations with respiratory enzymes and operates autonomously. Our latest data obtained on mitochondria of etiolated shoots of pea evidence the possibility of physical association between the respiratory supercomplexes and dimeric ATP-synthase. These data have allowed us to reconsider the contemporary concept of the phosphorylation system organization and propose a new subcompartmented oxphosomic model. According to this model, a substantial number of the OXPHOS complexes form oxphosomes, which in a definite stoichiometry include complexes I–V and are located predominantly in the cristae subcompartment of mitochondria in the form of highly organized strings or patches. These suprastructures represent “mini-factories” for ATP production. It is assumed that such an organization (1) contributes to increasing the efficiency of the OXPHOS system operation, (2) involves new levels of activity regulation, and (3) may determine the inner membrane morphology to some extent. The review discusses the proposed model in detail. For a better understanding of the matter, the history of development of concepts concerning the OXPHOS organization with the emphasis on recent contemporary models is briefly considered. The principal experimental data accumulated over the past 40 years, which confirm the validity of the oxphosomic hypothesis, are also provided.